2016
DOI: 10.1002/tea.21322
|View full text |Cite
|
Sign up to set email alerts
|

A day at the museum: The impact of field trips on middle school science achievement

Abstract: Field trips are an important feature of the United States' education system, although in the current context of high-stakes tests and school accountability, many schools are shifting resources away from enrichment. It is critical to understand how field trips and other informal learning experiences contribute to student test scores, but little research has explored the impact of field trips on standard measures of academic learning. In this study, I used 6 years of student-level data to estimate the impact of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 41 publications
0
32
0
8
Order By: Relevance
“…Recent studies show that informal environments can promote cognitive and affective outcomes but not necessarily simultaneously (e.g., Itzek‐Greulich et al, ; Peleg & Baram‐Tsabari, ; Whitesell, ; Wünschmann et al, ). Structuring fieldtrips to promote cognitive goals but compromise affective goals (including identity development) may undermine the potential of the informal setting in a schooling context to support science identities, especially for students like Nofar.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies show that informal environments can promote cognitive and affective outcomes but not necessarily simultaneously (e.g., Itzek‐Greulich et al, ; Peleg & Baram‐Tsabari, ; Whitesell, ; Wünschmann et al, ). Structuring fieldtrips to promote cognitive goals but compromise affective goals (including identity development) may undermine the potential of the informal setting in a schooling context to support science identities, especially for students like Nofar.…”
Section: Discussionmentioning
confidence: 99%
“…School visits to museums are relatively unexplored. Studies that have examined school visits focus on topics such as knowledge construction (Hong & Song, ), achievements (Whitesell, ), engagement with the exhibits (Laursen, ), and the affective or motivational effects (Stavrova & Urhahne, ). These studies have generally shown that science museums can support cognitive, affective, and motivational outcomes not only in free‐choice visits but also in school visits.…”
Section: Background and Conceptual Frameworkmentioning
confidence: 99%
“…Öğrencilerin okul dışında ortamlardan edindikleri bilginin (Bozdoğan ve Kavcı, 2016;Geveke, Steenbeek, Doornenbal ve Van Geert, 2016;Gutwill ve Allen, 2012) tutumları (Osborne, Simon ve Collins, 2003), motivasyonları ( Krombass ve Harms, 2008;Martin, Durksen,Williamson ve Ginns, 2016) üzerine olumlu etkileri ve farklı sosyoekonomik seviyelerden gelen öğrencilerin arasındaki farklılıkların azaltılması (Whitesell, 2016) açısından önemini araştırmacılar çalışmalarında göstermiştir. ( Ioannides ve Vosniadou, 2002, Rowell, Dawson ve Harry, 1990 Ancak mikroskobun "Bazı şeyleri yakından görmek için'' kullanıldığını yazmıştır.…”
Section: Conclusion and Discussionunclassified
“…Dolayısıyla okullarda tarih konularının öğretiminde okulda verilen eğitimin yanında okul dışı öğrenme ortamlarından mezarlıkların bir öğretim ortamı olarak kullanılması öğrencilerin akademik başarısını olumlu yönde etkilemektedir. Nitekim yapılan birçok araştırma; bilimsel gezilerin öğrencilerin akademik başarılarını olumlu yönde etkilediğini belirtmiştir (Şimşek, 2015(Şimşek, : Yeşilbursa, 2015Dilek, 2009;Şimşek, 2011;Şimşek ve Kaymakçı, 2015;Myers and Jones, 2003;Behrendt ve Franklin, 2014;Whitesell, 2015;Nadelson & Jordan, 2012;Akın, 2012;Rix ve McSorley, 1999;Demircioğlu, 2007;Knapp, 2000). Okul dışı öğrenme ortamlarından olan mezarlıklarla ilgili çeşitli veri toplama araçları geliştirilebilir ve uygulama çalışmaları yapılarak desteklenebilir.…”
Section: Alt Problemlerunclassified